2022
DOI: 10.1007/s10995-022-03551-x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and Cannabis Use During and After Pregnancy in California

Abstract: Objectives As the social and legal acceptance of cannabis use grows, health professionals must understand and mitigate the impact of cannabis use in the perinatal period. Here we compare the prevalence of tobacco and cannabis use during and after pregnancy in California, a state that recently legalized cannabis use. Methods Measures of tobacco and cannabis use during and after pregnancy were obtained from California’s Maternal and Infant Health Assessment, an annual pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Proximity or density of cannabis retailers was positively associated with detection of cannabis in two race/ethnicity groups (Hispanic and Asian Indian). A similar positive association was found with cannabis retailers and cannabis use in a study of Kaiser Permanente northern California prenatal patients-53% of whom were Hispanic or Asian/Pacific Islanders-in 2018, the first year that recreational cannabis was legalized [44]. It is not clear whether there were underlying differences in this association by race/ethnicity, as we found in our study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Proximity or density of cannabis retailers was positively associated with detection of cannabis in two race/ethnicity groups (Hispanic and Asian Indian). A similar positive association was found with cannabis retailers and cannabis use in a study of Kaiser Permanente northern California prenatal patients-53% of whom were Hispanic or Asian/Pacific Islanders-in 2018, the first year that recreational cannabis was legalized [44]. It is not clear whether there were underlying differences in this association by race/ethnicity, as we found in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Using 2017-2019 data from California's Maternal and Infant Health Assessment (MIHA), an annual population-based survey of California resident women with a live birth, Azenkot et al [44] found that cannabis use was more than twice as common as cigarette smoking among pregnant individuals (4.9% vs. 2.1%). These results were similar to those in our study in all race/ethnicity groups, except for Black and Native American subjects.…”
Section: Discussionmentioning
confidence: 99%